TUBG1 missense variants underlying cortical malformations disrupt neuronal locomotion and microtubule dynamics but not neurogenesis - Ivanova, Ekaterina L; Gilet, Johan G; Sulimenko, Vadym; Duchon, Arnaud; Rudolf, Gabrielle; Runge, Karen; Collins, Stephan C; Asselin, Laure; Broix, Loic; Drouot, Nathalie; Tilly, Peggy; Nusbaum, Patrick; et al. (Nature communications, 2019)
De novo heterozygous missense variants in the γ-tubulin gene TUBG1 have been linked to human malformations of cortical development associated with intellectual disability and epilepsy. Here, we investigated through in-utero electroporation and in-vivo studies, how four of these variants affect cortical development. We show that TUBG1 mutants affect neuronal positioning, disrupting the locomotion of new-born neurons but without affecting progenitors' proliferation. We further demonstrate that pathogenic TUBG1 variants are linked to reduced microtubule dynamics but without major structural nor functional centrosome defects in subject-derived fibroblasts. Additionally, we developed a knock-in Tubg1Y92C/+ mouse model and assessed consequences of the mutation. Although centrosomal positioning in bipolar neurons is correct, they fail to initiate locomotion. Furthermore, Tubg1Y92C/+ animals show neuroanatomical and behavioral defects and increased epileptic cortical activity. We show that Tubg1Y92C/+ mice partially mimic the human phenotype and therefore represent a relevant model for further investigations of the physiopathology of cortical malformations.
Keywords: Behavior, Animal; Mutation, Missense; modely nemocí na zvířatech; embryo savčí; Male; fibroblasty; Genetic Predisposition to Disease; missense mutace; Fibroblasts; Malformations of Cortical Development; konfokální mikroskopie; Gene Knock-In Techniques; mozková kůra; Embryo, Mammalian; centrozom; mužské pohlaví; neurony; epilepsie; Microtubules; HeLa buňky; elektronová mikroskopie; Cell Movement; Microscopy, Confocal; Animals; genový knockin; lidé; ženské pohlaví; myši transgenní; HeLa Cells; Humans; zvířata; mikrotubuly; Neurons; Microscopy, Electron; Intravital Microscopy; pohyb buněk; Disease Models, Animal; Mice, Transgenic; myši; chování zvířat; neurogeneze; tubulin; Epilepsy; Mice; malformace mozkové kůry; Female; intravitální mikroskopie; Centrosome; genetická predispozice k nemoci; Tubulin; Neurogenesis; Cerebral Cortex